Mechanical failure rates of artificial urinary sphincter components: Is the 3.5‐cm urethral cuff at higher risk?. Issue 1 (24th September 2018) - Loh‐Doyle, Jeffrey C.; Hartman, Natalie; Nazemi, Azadeh; Wayne, Kevin; Doumanian, Leo R.; Ginsberg, David A.; Boyd, Stuart D.
Abstract : Aim: We report the rates of artificial urinary sphincter (AUS) mechanical failure in a contemporary cohort of patients stratified by component type and size to determine if the 3.5‐cm cuff is at higher risk of failure. Methods: From 2005–2016, a total of 486 male patients with stress incontinence underwent implantation or revision of an AUS. 993 individual cases were retrospectively reviewed (465 primary placements and 528 revisions). Components were separately tallied and cases of mechanical failure were identified. Multiple variables including duration until failure and follow‐up interval were collected and analyzed for each malfunction. Results: After median follow‐up of 31.5 months, there were 48 distinct cases of mechanical failure. The urethral cuff was the most common component to fail ( n  = 27, 56.3%), followed by the pressure regulating balloon (PRB) ( n  = 6, 12.5%), tubing ( n  = 6, 12.5%), and the control pump, ( n  = 5, 10.4%). Four (8.3%) cases did not have the source of malfunction identifiable in available records though fluid loss was evident at the time of device interrogation. Sub‐analyses of cuff failure events showed that the 3.5‐cm cuff had a statistically significant higher risk of failure (HR: 7.313, ( P  < .0001) compared to larger cuff sizes. Conclusions: While each component is prone to malfunction, our study suggests that the 3.5‐cm urethral cuff is more susceptible to failure and failure events occur earlier after placement than larger cuff sizes.